QTL analysis and fine mapping of a major QTL and identification of candidate genes controlling curd setting height in cauliflower - Xiaoguang Sheng; Shiyi Cai; Yusen Shen; Huifang Yu; Jiansheng Wang; Shuting Qiao; Fan Lin; Honghui Gu (Vegetable Research)
Curd setting height, a critical component of plant height, plays an important role in ideotype construction and yield improvement in cauliflower. However, the underlying mechanisms governing this trait in Brassica crops remain unclear. In this study, we developed two F2 populations by crossing a cauliflower DH line, ZAASC4101, having a short main stem, with two Brassica oleracea inbred lines possessing a long main stem. Subsequently, two high-density linkage maps were constructed for each F2 population using a 10K MNP (multiple nucleotide polymorphism) array developed for Brassica oleracea species. These maps covered genetic distances of 8,373.66 and 8,250.01 cM, respectively. Notably, a major QTL related to curd setting height (BocDWARF1) was consistently identified on chromosome C01 with the highest LOD value in both F2 populations. Through the analysis of the recombinants identified from the F2:3 and F3:4 populations at the BocDWARF1 locus, we successfully fine-mapped this locus to a narrow interval delimited by SNP markers 1_40298271 and 1_40400283. This interval corresponds to an approximately 102-kb region harboring 12 predicted genes. Combined with parental resequencing data with HDEM reference genome annotation information, we proposed BolC1t04399H as the most promising candidate gene. This gene exhibits homology to the well-known plant height-controlling gene DWARF1 and shows a total of four nonsynonymous SNPs in the exon region between the parents. This study lays the foundation for map-based cloning of BocDWARF1 and provides valuable insights for breeding improved cauliflower varieties with the ideal curd setting height.